A modified high-yield method for primary culture of rat retinal microglial cells. (February 2022) - Han, Xiaokun; Liu, Xuan; Zhuang, Jiejie; Liang, Xida; Luo, Qian; Chen, Pei; Wen, Ye; Wang, Xiao; Peng, Juan; Yang, Ying; Sha, Xiangyin; Zhuang, Jing
Abstract: Microglial cells are the main immune cells of the retina. The primary culture of the retinal microglia is critically important in investigating the cells' properties and behaviors in neurodegenerative and inflammatory retinal disease. Here, we described a modified protocol of a microglial cell culture from the neonatal rat retina. In our culture protocol, the retina was isolated from the neonatal rat eye from postnatal day 1 to day 3 and trypsinized into a single-cell suspension. The cells were seeded into a T75 flask, which was pre-coated with poly-D-lysine (PDL) and cultured with dulbecco's modified eagle medium-F12 (DMEM/F12) that contained 10% fetal bovine serum (FBS) with different concentrations. Small bright rounded cells were observed on the top of mixed glial cells on the seventh day, and attained the maximum cell number on the 14th day. Then, the isolation was performed by a shaking method and isolated cells were identified with microglia markers ionized calcium-binding adaptor molecule 1 (IBA1), transmembrane protein 119 (TMEM119), cluster of differentiation 11b (CD11b), as well as astrocyte marker glial fibrillary acidic protein (GFAP) by immunofluorescence staining. Additionally, the initial plating ratio of the mixed glial cell, culture period of isolation, procedures of the isolation, as well as the purification procedure, were optimized for our primary microglial cell culture. The morphological changes and phagocytic function were performed after lipopolysaccharide (LPS) stimulation. Moreover, the release of pro-inflammatory cytokines at different time points of LPS activation were measured. In the present study, we found that the concentration of one retina/T75 flask could harvest the largest number of microglial cells. Besides, we continuously cultured the mixed glial cells as long as one month and isolated the mixed glial cells as much as three times. In our study, we used an isolation-shaking rate of 200 rpm for 2h, which guaranteed the steady rate and resulted in high purification of the primary retinal-microglial cells, with no need of an additional purification procedure. In conclusion, we provided a high-producing protocol for the primary culture of purified rat retinal-microglial cells. Graphical abstract: Image 1